PERBEDAAN PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TIPE II DENGAN PEMBERIAN RELAKSASI OTOT PROGRESIF DAN SENAM KAKI DIABETES - Sellynia Herwin Julieta; Hartono, Hartono; Sunarto, Sunarto (Tahta Media Group, 2023)
Diabetes mellitus a serious chronic disease, which the pancreas is unable to produce insulin in the body, but it can also occur if the body is not effective in using the insulin produces. One of the non-pharmacological management of diabetes mellitus is progressive muscle relaxation and diabetic foot exercise. purpose of the Research: Analyze the difference in the effect of progressive muscle relaxation and foot exercises on reducing blood sugar patients with type II diabetes mellitus.Research methodology: The study used the Quasi Experimental Design method with a Static Group Comparison Design. The sample of this study was type II diabetes mellitus in the Sidoharjo Health Center, Sragen, as many as 56 respondents. Sampling using purposive sampling technique. Results: The results of the Independent Sample T-Test on progressive muscle relaxation and diabetic foot exercises showed Sig. (2-tailed) p = 0.777 where p value > 0.05. Discussin, Progressive muscle relaxation and diabetic foot exercises can be a complementary therapy to diet and pharmacology to help lower blood sugar levels. Conclusions: There is no significant difference between progressive muscle relaxation therapy and diabetic foot exercises in reducing blood sugar levels in type II diabetes mellitus patients